2023
DOI: 10.1021/acs.jcim.3c01267
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Medin Folding and Dimerization Dynamics and Conformations via Atomistic Discrete Molecular Dynamics Simulations

Fengjuan Huang,
Xinjie Fan,
Ying Wang
et al.

Abstract: Medin is a principal component of localized amyloid found in the vasculature of individuals over 50 years old. Its amyloid aggregation has been linked to endothelial dysfunction and vascular inflammation, contributing to the pathogenesis of various vascular diseases. Despite its significance, the structures of the medin monomer, oligomer, and fibril remain elusive, and the dynamic processes of medin aggregation are not fully understood. In this study, we comprehensively investigated the medin folding and dimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…A recent study directly illustrated that the creation of a β-barrel oligomer caused membrane leakage in in silico . The formation of β-barrel intermediates was also supported in the aggregation of full-length Aβ, , hIAPP, , human calcitonin (hCT), , and medin in silico and in vitro . The β-barrel structure formed by full-length Aβ was also determined by a cryo-EM assay .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…A recent study directly illustrated that the creation of a β-barrel oligomer caused membrane leakage in in silico . The formation of β-barrel intermediates was also supported in the aggregation of full-length Aβ, , hIAPP, , human calcitonin (hCT), , and medin in silico and in vitro . The β-barrel structure formed by full-length Aβ was also determined by a cryo-EM assay .…”
Section: Resultsmentioning
confidence: 91%
“…The β-barrel oligomer, initially discovered in an 11-residue segment of αB-crystallin and frequently observed in toxic amyloid fragments and full-length peptide aggregation simulations, ,,, was proposed as a potentially cytotoxic oligomer in amyloidosis. Our prior simulation studies have demonstrated that the β-barrel oligomer was a common intermediate in the fibrillization of toxic amyloid segments (e.g., NACore, hIAPP 8–20 , hIAPP 19–29 , SOD1 28–38 ) but absent in the aggregation of nontoxic amyloid fragments (e.g., hIAPP 15–25 , SOD1 28–38 G33W39 , SOD1 28–38 G33V39 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These evaluations were conducted using standard MD simulations employing an explicit solvent model in previous investigations. , Furthermore, recent simulations encompassing amyloid aggregation phenomena, including those of calcitonin peptides (hCT, sCT, phCT, DM-hCT, and TL-hCT) , and amylin peptides (hIAPP, hIAPP­(S20G), and rIAPP), ,, have successfully mirrored experimentally observed variations in amyloid propensity and secondary structures. Given its rapid computational speed and improved sampling efficiency, DMD has emerged as a popular tool for investigating protein folding and aggregation dynamics, both within our research group and in the broader scientific community. …”
Section: Methodsmentioning
confidence: 99%